Nate the Great and the phony clue - Sharmat, Marjorie Weinman (Random House Children's Books, 2010)
When he finds a torn piece of paper with only part of a word on it, boy detective Nate sets out to find the missing pieces. Includes related facts, jokes, recipes, and activities.